THE HISTORY OF QIRA’AT SAB’AH IN BIMA (HISTORICAL STUDY) - Mubaraq, Fitratul; M, M. Dahlan; Firdaus, Firdaus (Jurnal Diskursus Islam, 2020)
This article is about the development of Qirā’at Sab’ah in Bima (a historical study). The aim is: 1) To explain the the early history of  Qirā’at Sab’ah in Bima; 2) to explain the expansion process of Qirā’at Sab’ah in Bima; 3) to find the prominent figures involved in the spread of Qirā’at Sab’ah in Bima; 4) to explain the people’s response in learning Qirā’at Sab’ah in Bima. This article is using descriptive qualitiaitve method with a historical approach. The result shows that Qirā’at Sab’ah was started along with the beginning of Islam in Bima. Back then, Qirā’at Sab’ah was learned limited to particular people only. Only those who are concern to learn about it. The first and often recited was Imam Ashim narrated by Hafs. There are two process of Qirā’at Sab’ah spread. Firstly, prior to MTQ competition. Here, the Qirā’at Sab’ah appeared only a learning process between students and the teacher. Secondly, post MTQ competition. At this time, Qirā’at Sab’ah has begun learned by widspread of people who eventually will compete at the MTQ festival. As it stands, the number of people who learn Qirā’at Sab’ah is decreasing. As a part of MTQ competiton, Qirā’at Sab’ah is notorious among Bima people. The key figure of Qirā’at Sab’ah spread in Bima are TGH Husein, TGH Abubakar, TGH Yusuf, TGH Ramli, TGH Ridwan, TG Jubair, TGH Adnin and many more involved in the spread, especially the students of High School of Islamic Studies (PTIQ) and Bima students in Al-Azhar University of Cairo, Egypt. When first introduced, Qirā’at Sab’ah the people of Bima claimed it was an error in reciting Quran. But in time, people get used to it, especially when it began to present in MTQ.